The Effect of Using the Snowball Throwing Learning Model on Third Grade Elementary School Students' Indonesian Language Learning Outcomes: Pengaruh Penggunaan Model Pembelajaran Snowball Throwing Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas III SD - Metri Revidawati; Farida Ariani; Joni Indra Wandi; Firda Khairati Amris; Syamsurizal Syamsurizal (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This study was motivated by the low Indonesian language learning outcomes of third-grade students at SD Negeri 07 Lubuk Alung, which were caused by a monotonous learning model, low student engagement, and scores that were still below the Learning Objective Achievement Criteria (KKTP). This study aimed to examine the effect of the Snowball Throwing learning model on students' Indonesian language learning outcomes. This research is quantitative in nature with a quasi-experimental design of the nonequivalent control group type. The research population includes 50 students divided into classes III A and III B. The data collection instrument is in the form of a learning outcome test, which is then analyzed using normality tests, homogeneity tests, and hypothesis tests (t-tests). The results of data analysis through the independent sample t-test showed a Sig. (2-tailed) value of 0.018 < 0.05. This finding shows that Ho is rejected and Ha is accepted, which means that there is a significant effect of using the Snowball Throwing model on improving student learning outcomes. The results of this study can be concluded that the Snowball Throwing learning model is proven to be effective in improving Indonesian language learning outcomes at the elementary school level. The implications of this study suggest that teachers apply a variety of active learning models to overcome student boredom and optimize the achievement of learning objectives.